Hypoxia Inducible Factor-1-Alpha Expression on Preeclampsia Mice Model With L-Arginine Administration - Anggraini, Nutria Widya Purna; Sulistyowati, Sri; Bachnas, Muhammad Adrianes; Yuliantara, Eric Edwin; Prabowo, Wisnu; Budihastuti, Uki Retno (Folia Medica Indonesiana, 2021)
Preeclampsia is hypertension in pregnancy that aï¬€ects 2% to 8% of pregnancies worldwide and causes significant maternal and perinatal morbidity and mortality. In the pathogenesis of preeclampsia, placental hypoxia plays an important role, associated with excessive trophoblast apoptosis resulting in decreased trophoblast and spiral arteries invasion. This placental hypoxic condition will induce increased expression of Hypoxia Inducible Factor -1-Alpha (HIF-1-A). L-Arginine is a potent vasodilator presumably to improve preeclampsia placental hypoxic conditions and reduce HIF-1-A expression. This study was an experimental study with a parallel-group post-test only design. Thirty-six preeclamptic mice models were divided into 2 groups. The control group (K1) 18 preeclamptic mice model without treatment and the treatment group (K2) 18 preeclamptic mice given L-Arginine. The independent variable was the administration of L-Arginine and the dependent variable is the placental HIF-1-A expression. Statistical analysis used unpaired t-test on normal data distribution, and Mann Whitney test on abnormal data distribution. The mean of placental HIF-1-A expression K1 was 2.47 ± 1.65 with a minimum value of 0.4 and a maximum value of 6.6. At K2 0.93 ± 0.55 with a minimum value of 0.0 and a maximum value of 2.0. Statistical tests showed that the placental HIF-1-A expression in the treatment group was significantly lower than that in the control group (p <0.001). In conclusion, the expression of HIF-1-A in preeclamptic mice model placenta decreased with L-Arginine administration.